Response strategies of the main forest types to climatic anomalies across Croatian biogeographic regions inferred from FAPAR remote sensing data (Forest Ecology and Management, 2014)
Croatia is positioned in the transitional zone of South-eastern Europe and the Mediterranean, a region with frequent occurrence of severe droughts and dry spells, which makes it particularly vulnerable to the impact of climate change. It distends across three main European biogeographical regions – Continental, Alpine and Mediterranean – and therefore has a very high level of forest diversity comprised of 11 out of 14 European forest types. This makes it very convenient to study the exposure of main European forest types to extreme climatic events in the southern limits of their species distribution range. This study provides an assessment of responses of forest vegetation under episodes of climatic anomalies consisting of the most severe historical dry and warm spells in 2000 and 2003, together with the extremely rainy season in 2005 across Croatian territory. The question of interest in this study was to reveal how the existing forest types across the territorial gradient respond to highly expressed extreme climatic variations and to infer some clues about related adaptive strategies. The regional scale approach was applied which previously performed structural delineation of forest cover into eleven main forest groups or bioclimates and were examined considering functional differences. Responses of eleven bioclimatic types were analyzed by time series (1998–2005) of monthly FAPAR (The Fraction of Absorbed Photosynthetic Active Radiation) coverage with a spatial resolution of 1.2km, freely available from JRC FAPAR project. To quantify and differentiate the vegetation response in the considered years we adopted indices of resilience (resistance, recovery, resilience and relative resilience). We also provided a modified approach by applying these indices on a seasonal scale to examine the relationship between variations of phenology and ecosystem responses. The results confirmed the modification of seasonality of photosynthetic activity in relation to the altitudinal and spatial gradient. At the intra-seasonal scale, we distinguished specific opportunistic behavior of the common beech and oak forest types to alternating climatic conditions. Beech forest types show a very high ability to shift their phenology to earlier spring warming as a consequence of global warming. However, continental and Mediterranean oak forest types and in particular Aleppo pine and holm oak forests showed a higher increase of FAPAR during rainy events. The revealed capability of some tree species to better exploit rainfall in very wet periodic episodes has to be further evaluated in drawing conclusions about the overall resilience of forests under future climate change scenarios.